2012
DOI: 10.1021/ie202077g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications in Styrene–Butadiene Rubber after Microwave Devulcanization

Abstract: Microwave devulcanization has been studied as a method for elastomer recycling, which is based on the conversion of the reticulated and infusible structure of thermosetting rubbers in free polymeric chains able to be remolded by thermomechanical processing in recycling operations for the manufacture of other products. Elastomeric wastes are often irregularly discarded in nature, producing serious environmental damage, and their mechanical recycling is still considered a challenge. Thus, the development of alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 20 publications
3
66
0
Order By: Relevance
“…It is also interesting to notice that the bands at 1076, 1029 and 1006 cm -1 , which are related to C-S bonds, are seen mainly in the GTRv and GTR3 samples. Hirayama and Saron [25] also noticed changes in the intensity bands in the SBR samples most exposed to microwaves. The authors observed that polysulfidic bonds were broken, however the monosulfidic bonds remained preserved.…”
Section: Chemical Propertiesmentioning
confidence: 84%
See 2 more Smart Citations
“…It is also interesting to notice that the bands at 1076, 1029 and 1006 cm -1 , which are related to C-S bonds, are seen mainly in the GTRv and GTR3 samples. Hirayama and Saron [25] also noticed changes in the intensity bands in the SBR samples most exposed to microwaves. The authors observed that polysulfidic bonds were broken, however the monosulfidic bonds remained preserved.…”
Section: Chemical Propertiesmentioning
confidence: 84%
“…According to spectra (Figure 2), the intensities of some bands were altered with the devulcanization process. Previous studies have attributed these IR bands to: (1) 1537 cm -1 : stretching vibration of a methyl-assisted conjugated double bond (" -(C=C) n -, where n > 6) from both NR [30,31] and SBR [32]; (2) deformation from NR rubber [31]; (3) 1076 cm -1 : symmetric C-S-C group stretching vibrations in the two C-S bonds [33]; (4) 1029 and 1006 cm -1 : C-S bonds [25]; (5) 962 cm -1 : -CH=CH-group vibrations of butadiene present in SBR [33,34]; and (6) 828 cm -1 : $ C-H bending from NR rubber [31]. The results reveal that the samples most exposed to microwaves had lower intensity bands, which was more evident in the GTR7 sample.…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the ML value is proportional to the initial viscosity of the sample [19] , the increase of the exposure time to microwaves reduced the viscosity of rubber induced by the breaking of the three-dimensional network of the vulcanized GTR. The sample GTR3 presented the highest ML value probably due to the formation of new bonds in the rubber, since during sample exposure to microwaves, bonds can be broken and created at the same time [20] . Therefore, depending on the time at which the sample was exposed to microwaves, the former event can exceed the later one or vice-versa.…”
Section: Revulcanization Characteristicsmentioning
confidence: 99%
“…Devulcanization is a way of providing energy to destroy, total or partially, the three-dimensional network formed during vulcanization 4 . The known methods that use different ways to promote the devulcanization of rubber include thermomechanical, thermo-chemical and mechano-chemical [5][6][7][8][9] , physical (by microwaves 3,[10][11][12][13][14][15][16][17][18][19][20] and ultrasound [21][22][23][24][25][26][27][28][29] ) and biochemical [30][31][32][33] . All of them involve complex transformations that lead to depolymerization, oxidation, and in many cases, the degradation of polymeric chains of rubber, with the consequent reduction on its viscosity 34 .…”
Section: Introductionmentioning
confidence: 99%